Dynamic redistribution of paxillin in bovine osteoblasts stimulated with adenosine 5′-triphosphate - Silber, Ann-Sophie (Springer Netherlands, 2012)
Exposure to extracellular 5′-adenosine triphosphate (ATP) is known to induce membrane blebbing. In this study, we investigated the subcellular distribution of the cytoskeletal adaptor protein paxillin in primary bovine osteoblasts upon stimulation with ATP. Cells expressing a fusion protein of green fluorescent protein (GFP) and paxillin were followed by time-lapse video-microscopy after stimulation with 100 μM ATP. Within 100 s, GFP-paxillin became incorporated in numerous de novo formed focal aggregates localized at the cell periphery. The assembly of individual paxillin-containing aggregates occurred with a mean half-life time of <60 s, whereas their disassembly lasted twice as long. Despite the ongoing presence of ATP, the formation of paxillin aggregates was self-limiting within 25 min. Paxillin clustering was preceded by a transient rise in cytoplasmic calcium transients, which peaked already 20 s after adding ATP. The high mobility of paxillin was confirmed by measuring the dissociation rate of GFP-paxillin at mature focal adhesions, demonstrating the presence of a highly mobile fraction with a mean recovery half-life of 8.2 ± 1.2 s, followed by a slower phase (53 ± 20 s). Thus, both the exchange of paxillin at mature focal adhesions and the increase in intracellular calcium concentrations upon ATP stimulation are very rapid processes, which override the time course of ATP-induced paxillin membrane clustering by one to two orders of magnitude. Our data demonstrate that the transient recruitment of paxillin in membrane protuberances is based on the high intracytoplasmic mobility of unbound paxillin molecules and their rapid focal accumulation.